2019
DOI: 10.1002/cam4.1996
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of vitamin D biosynthesis and pathway target genes reveals UGT2A1/2 and EGFR polymorphisms associated with epithelial ovarian cancer in African American Women

Abstract: An association between genetic variants in the vitamin D receptor ( VDR ) gene and epithelial ovarian cancer (EOC) was previously reported in women of African ancestry (AA). We sought to examine associations between genetic variants in VDR and additional genes from vitamin D biosynthesis and pathway targets ( EGFR, UGT1A, UGT2A1/2, UGT2B, CYP3A4/5 , CYP2R1 , CYP27B1 , CYP24A1 , CYP11A1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…Davies found that AKT1 (E17K) mutations were effective therapeutic targets for AKT inhibitors [53], although combinations with other targeted agents may be required where activating oncogenic mutations of other proteins were present in the same tumour [54]. Furthermore, alterations in EGFR have been found to perturb enzyme efficacy and proliferation in ovaries and impact susceptibility to OC [55]. COL6A3 was shown to be upregulated in ovarian cancer [56].…”
Section: Discussionmentioning
confidence: 99%
“…Davies found that AKT1 (E17K) mutations were effective therapeutic targets for AKT inhibitors [53], although combinations with other targeted agents may be required where activating oncogenic mutations of other proteins were present in the same tumour [54]. Furthermore, alterations in EGFR have been found to perturb enzyme efficacy and proliferation in ovaries and impact susceptibility to OC [55]. COL6A3 was shown to be upregulated in ovarian cancer [56].…”
Section: Discussionmentioning
confidence: 99%
“…A study on 170 cases of epithelial ovarian cancer compared to healthy controls found no association between the ApaI polymorphism and ovarian cancer risk [33]. In another case control study, the ApaI polymorphism was associated with increased risk of ovarian cancer in African-American women [81]. Other researchers reported that the ApaI polymorphism seems to be associated with ovarian cancer in women with higher predicted 25(OH)D levels but not in women with lower predicted levels [82].…”
Section: Vitamin D Receptormentioning
confidence: 98%
“…The ApaI polymorphism has also been investigated and case control studies have provided mixed results [12,33,37,81]. A study on 170 cases of epithelial ovarian cancer compared to healthy controls found no association between the ApaI polymorphism and ovarian cancer risk [33].…”
Section: Vitamin D Receptormentioning
confidence: 99%
“…The status of excess nutrition called obesity has been proven in many studies as a risk factor for cancer, and physical activity is a factor in reducing obesity because it is the primary determinant in energy expenditure so that it can reduce the risk of cancer caused by obesity (11)(12)(13)(14). That is stated in a study related to risk factors that predict cancer cell growth: smoking, diet, alcohol consumption, reproduction (pregnancy, breastfeeding, age at first menstruation, menopause), obesity, and lack of physical activity (8,10,15,16). ).…”
Section: Introductionmentioning
confidence: 99%